The Influence of Perceived Benefits, Trust, Perceived Risk, and Perceived Ease of use on Purchase Intentions on the Tiktok Shop Application - Wahyu Ghani Febri Setioko; Dian Widyaningtyas; Purnadi; Arini Hidayah (Indonesian Journal of Business Analytics, 2026)
The development of social commerce has driven significant changes in online shopping behavior. One platform that integrates entertainment and shopping features into a single platform is TikTok Shop. This study aims to analyze the influence of perceived benefit, trust, perceived risk, and perceived ease of use on purchase intention on TikTok Shop in Kebumen Regency. The method used is a quantitative approach using a survey technique involving 150 respondents selected through purposive sampling. Data testing was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM).This study provides implications for business actors and platform developers to improve features that strengthen the perception of benefits, ease of use, and risk mitigation in order to encourage consumer purchase intention on social commerce platforms.